T1rho, T2, and T2* relaxation time based on grading of intervertebral disc degeneration. (March 2023) - Takashima, Hiroyuki; Yoshimoto, Mitsunori; Ogon, Izaya; Takebayashi, Tsuneo; Imamura, Rui; Akatsuka, Yoshihiro; Yamashita, Toshihiko
Background: Previous studies have explored the biochemical changes of disc degeneration and its relevance in low back pain using various quantitative magnetic resonance imaging (MRI) techniques. However, quantitative evaluation of intervertebral disc (IVD) with MRI such as T1rho, T2, and T2* have not been previously analyzed and compared directly in the same patients. Purpose: To investigate T1rho, T2, and T2* of IVD degeneration in the same patients, reveal the correlation coefficients of these values, and evaluate which values are more sensitive to detect the degree of IVD degeneration. Material and Methods: The participants were 55 patients who underwent MRI examinations which the investigator classified the degree of IVD degeneration according to the Pfirrmann classification. The T1rho, T2, and T2* values of IVD were analyzed for their classification and were compared. Results: T1rho, T2, and T2* values were 74.3 ± 7.1, 61.2 ± 6.7, and 46.5 ± 16.3 ms (grade II); 61.6 ± 11.8, 48.9 ± 8.2, and 34.1 ± 11.8 ms (grade III); 50.8 ± 10.8, 38.9 ± 9.8, and 25.4 ± 8.1 ms, (grade IV); 44.5 ± 13.3, 34.8 ± 9.5, and 11.2 ± 6.6 ms (grade V), respectively. Those values significantly decreased with increasing grades, but T1rho and T2 values for grades IV and V were not different. Conclusion: The T1rho and T2 values were excellent for the evaluation of initial to moderate IVD degeneration with water and proteoglycan content. In contrast, the T2* value was suitable for detailed evaluation of progressive IVD, even with poor water content.